Dissolution Effectiveness of Moringa Leaf Pills (Moringa Oleifera L.) and Aloe Vera (Aloe Barbadensis Miller) - Ariyanti Ariyanti; Eni Masruriati; Dwi Setyowati; Filza Mazaya Nurulita (Global Health Science Group, 2022)
Oral preparations with level solubility tall so speed dissolution substance active from form preparations Becomes more fast, anyway with preparations with speed dissolution low so speed dissolution substance active from form preparations Becomes slow, so rate absorption drug more slow as well as produce bioavailability low. Materials potion drug traditional for example from ingredient plant natural around which not yet experience processing whatever. Ingredient nature used _ as drug traditional in study this is plant leaf moringa and tongue crocodile. Leaf Moringa (Moringa oleifera L.) has various type effect therapy like antimicrobial, anticancer, anti-inflammatory, effect antidiabetic as well as as antioxidants. Compound chemical in the leaves _ moringa that is there is polyphenols, acids phenolics, flavonoids, glucosinolates, alkaloids, vitamins, acids phenolics, isothiocyanates, tannins and saponins. Plant tongue crocodile (Aloe barbadensis Miller). kindly chemistry, tongue crocodile consists over 90% water and 4% carbohydrates, the rest consists of minerals, 17 kinds amino acids. Gel found on the tongue crocodile there is content substance antibacterial as well as possible antifungal _ stimulate tiroblast . Study this aim for knowing effectiveness dissolution pill from leaf moringa and tongue crocodile with use method study experimental. Result of study this yield extract leaf moringa and tongue crocodile obtained on the leaves moringa by 6.38% and tongue crocodile 6.268%. Assessment test preparations pill Fulfill condition uniformity weight and fulfill dissolution test conditions because time the required crush for 30 minutes.